Knowledge of Nurses on Systematization of Nursing Care in the context of head and ceck cancer surgery (Research, Society and Development, 2020)
The objective was to analyze the nurses' knowledge about the Nursing Care Systematization (SAE) in head and neck cancer surgery. This is a descriptive research, with a qualitative approach, with the participation of 5 nurses working at the Center for High Complexity Assistance in Oncology (CACON) located in Belém-PA, using an interview technique to assess the applicability and operationalization of the SAE to head and neck post-surgery patients. A semi-structured script with open questions and for recording the interview was used on a cell phone. The data were analyzed according to Bardin in the form of pre-analysis, exploration of the material and treatment of the results. The study was approved by the Research Ethics Committee under CAAE: 82427318.5.3001.5550. According to the study, it was possible to identify 3 categories and, from the analysis, it was noticed that each participant had different degrees of difficulty, prevailing or recording in association with the SAE with the nursing process (NP). In addition, it became noticeable the absence of updates on the steps that comprise the NP, therefore, trained professionals have difficulties in correctly and sequentially implementing the process steps, or which part of the SAE. However, in general, nurses recognize the nursing process as a method of theoretical-practical articulation. Conclude if the participants of this study demonstrated little knowledge about the theme explored, even though this is part of their work process.